The Many Facets of Hypoxia in Plants - Loreti, Elena (Plants (Basel), 2020)
Plants are aerobic organisms that require oxygen for their respiration. Hypoxia arises due to the insufficient availability of oxygen, and is sensed by plants, which adapt their growth and metabolism accordingly. Plant hypoxia can occur as a result of excessive rain and soil waterlogging, thus constraining plant growth. Increasing research on hypoxia has led to the discovery of the mechanisms that enable rice to be productive even when partly submerged. The identification of Ethylene Response Factors (ERFs) as the transcription factors that enable rice to survive submergence has paved the way to the discovery of oxygen sensing in plants. This, in turn has extended the study of hypoxia to plant development and plant–microbe interaction. In this review, we highlight the many facets of plant hypoxia, encompassing stress physiology, developmental biology and plant pathology.